ANALISIS WACANA KRITIS ATAS PERNYATAAN SIKAP GERAKAN ISLAM DI INDONESIA TERHADAP ISIS - Zainal Fikri (Alhadharah: Jurnal Ilmu Dakwah, 2018)
This article analyzes the statements of seven Islamic movements in Indonesia towards ISIS, namely JAT, JAS, HTI, FPI, FUI-MUI, Muhammadiyah and NU with the Critical Discourse Analysis - CDA) approach from Teun Van Dijk. This study found that groups who aspire to establish the Khilafah Islamiyah such as JAT, JAS, HTI, and FPI, basically, they agreed with the establishment of the Islamic Caliphate, but differed on methods and strategies with ISIS to achieve the establishment of the Khilafah Islamiyah. These diverse strategies and ideologis are keys to their different attitudes  towards ISIS. The groups that are firmly loyal to the nation-state of Indonesia reject the form of the Khilafah Islamiyah state. Therefore they expressly reject ISIS and its Islamic Caliphate declaration. Included in this group are mass organizations joined in the FUI-MUI, including Muhammadiyah and NU